2020
DOI: 10.1021/acs.chemrev.9b00556
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Substrates by Nitrogenases

Abstract: Nitrogenase is the enzyme that catalyzes biological N2 reduction to NH3. This enzyme achieves an impressive rate enhancement over the uncatalyzed reaction. Given the high demand for N2 fixation to support food and chemical production and the heavy reliance of the industrial Haber–Bosch nitrogen fixation reaction on fossil fuels, there is a strong need to elucidate how nitrogenase achieves this difficult reaction under benign conditions as a means of informing the design of next generation synthetic catalysts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
375
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(383 citation statements)
references
References 262 publications
6
375
1
1
Order By: Relevance
“…The different hydrogen kinetic isotope effects (KIEs) for H 2 production by Mo-nitrogenase compared to CH 4 production by the V- and Fe-only nitrogenases could be due to different 1 H selectivities by each isoform or due to different contributions by the protonated thiols (orange) compared to the bridging Fe-hydrides (green) for reduction of different substrates (e.g., N 2 versus CO 2 ). For instance, it has been suggested that CO 2 can migrate into the Fe-hydride bond ( 70 , 94 ), although it is not known at which E n state this might occur or whether this is necessarily the only pathway for CO 2 reduction to methane. Modified from reference 73 with permission.…”
Section: Resultsmentioning
confidence: 99%
“…The different hydrogen kinetic isotope effects (KIEs) for H 2 production by Mo-nitrogenase compared to CH 4 production by the V- and Fe-only nitrogenases could be due to different 1 H selectivities by each isoform or due to different contributions by the protonated thiols (orange) compared to the bridging Fe-hydrides (green) for reduction of different substrates (e.g., N 2 versus CO 2 ). For instance, it has been suggested that CO 2 can migrate into the Fe-hydride bond ( 70 , 94 ), although it is not known at which E n state this might occur or whether this is necessarily the only pathway for CO 2 reduction to methane. Modified from reference 73 with permission.…”
Section: Resultsmentioning
confidence: 99%
“…It is even less active than V-nitrogenase and seems to be only expressed in Mo- and V-deficient conditions. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…Nitrogenases reduce a range of multibond compounds (Hu et al 2011, Yang et al 2011, Lee et al 2010, Zheng et al 2018, and this quality is shared across different nitrogenases (Seefeldt et al 2020). Although DPOR and COR were expressed and present in all metatranscriptomes and metagenomes, expression of both was an order of magnitude higher in the UC4 experiment compared with the LG5, LG6, and L7 experiments (with the exception of COR in LG5).…”
Section: Evidence For Methane Production By Cyanobacteria and Proteobmentioning
confidence: 95%